Transesterifikasi Minyak Goreng Bekas Dengan Katalis ZnO Sintesis Dari Presipitan Zinc Oksalat ; Pengaruh Variasi Rasio Mol Reaktan Dan Jumlah Katalis - Deni Afrika; Yusnimar Yusnimar; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Curently various types of catalysts have been investigated for the production of biodiesel from high free fatty acid feedstock. Waste Cooking Oils with high free fatty acid (FFA) can be used as a feedstock for biodiesel production. Various types of catalysts have been investigated for the production of biodiesel from high FFA feedstock. This research aims to sinthesize ZnO catalyst from ZnC2O4 presipitation. This catalyst was used for transesterification of CPO with high FFA into biodiesel. Then, the effect of variations in mole ratio of reactants and variations in the amount of catalyst on the yield of biodiesel produced will be studied. FFA content in the waste cooking oils is 8,16%. Therefore, Biodiesel production process was carried out with a two-stage reaction that was esterification and transesterification. The esterification reaction was held time 60 minutes at temperatures 65oC with H2SO4 catalyst as much as 1% w/w of oil. The transesterification reaction was held time 120 minutes at temperatures 65oC; the mole rato of oil : methanol were 1:6, 1:12, 1:18; ZnO catalyst amount were 0,3%, 0,4% and 0,5%; . The higest yield obtained was 92,12% in process with 1:18 in oil : methanol mole ratio and 0,5% catalyst amount. The produced biodiesel has density 867,8 kg/m3, viscosity 5,25 mm2/s, flash point 175oC, acid value 0,547 mg-KOH/g-biodiesel, saponification value 40,766 mg-KOH/g-biodiesel and alkyl ester content 98,647%.Keywords: biodiesel, esterification, transesterification, waste cooking oils, ZnO